Structure of integrated supersymmetric nonlinear dynamic systems on the reduced invariant subvarieties - Pritula , M. M.; Kuibida , V. S. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Based on an analysis of a supersymmetric extension of the algebra of pseudodifferential operators on $\mathbb{R}^1$  an infinite hierarchy of supersymmetric Lax-integrable nonlinear dynamical systems is constructed by means of the Yang-Baxter $\mathfrak R$-equation method. The structure of these systems on reduced invariant submanifolds specified by a natural invariant Lax-type spectral problem is investigated.